UPAYA INDONESIA SEBAGAI NEGARA DI KAWASAN CORAL TRIANGLE DALAM KONSERVASI TERUMBU KARANG DI WAKATOBI - Suba, Almadhea; Marzaman, Atika Puspita (Pusat Studi Ekonomi Publikasi Ilmiah dan Pengembangan SDM Azramedia indonesia, 2024)
Wakatobi as one of the areas in the coral triangle is home to hundreds of coral reef species and also other marine biota. The massive marine biota in this area made Wakatobi designated as a national park in 2002 and since then various coral reef conservation efforts have been carried out since it was designated as a national park. This research describes the significance of coral reefs in Wakatobi from an ecological and economic perspective, the challenges faced in coral reef conservation, ranging from natural factors to inadequate infrastructure that cannot maximize the potential of this area, to efforts made for coral reef conservation through programs and international cooperation. This research used descriptive qualitative method. The results found that the Wakatobi national park area has great potential, but requires collaboration from various parties to maximize the existing potential so that efforts made by Indonesia in coral reef conservation must involve various actors ranging from local communities to collaboration between ministries and international organizations to maximize the potential of this region because coral reefs play a significant role in the development of marine life around it.